Analgesic efficacy of serratus anterior plane block v/s thoracic paravertebral nerve block in video-assisted thoracoscopic surgeries: A prospective randomized study - Jaya Lalwani; Sonali Sahu; Vritika Manghnani (Медицина болю)
Background: Multimodal analgesia plays a vital role for adequate pain relief in postoperative period including regional nerve blocks in video-assisted thoracoscopic surgeries. The study aims to compare the analgesic efficacy of serratus anterior plane block and thoracic paravertebral nerve block using ultrasound guidance in VATS.